The Law, the State, and other political writings, 1843-1850 - Bastiat, Frédéric, 1801-1850 (Bastiat, Frédéric, 1801-1850. Works. 2011., 2012)
Frederic Bastiat (1801-1850) was a keen observer of political and economic problems and a passionate proponent of liberal economic theory. This book collects nineteen of Bastiat's articles, ranging from the theory of value and rent, public choice and collective action, government intervention and regulation, the balance of trade, education, and trade unions to price controls, capital and growth, and taxation. Throughout his articles, Bastiat demonstrates how the combination of careful logic, consistency of principle, and clarity of exposition is the instrument for solving most economic and social problems. In his famous essay "The Law" Bastiat explains that the law, far from being what it ought to be, "namely the instrument that enabled the state to protect individuals' rights and property", had become the means for what he termed "spoliation" (or plunder). From the article "The State" written at the height of the 1848 Revolution in June, comes perhaps his best-remembered quotation: "The state is the great fiction by which everyone endeavours to live at the expense of everyone else." In this volume, readers will find extensive introductory material, including notes on the translation and on the editions of the oeuvres completes, a chronology of Bastiat's life and works, two maps of France showing the cities associated with Bastiat, annotations to the articles, and a bibliography. A special section provides charming, little-known anecdotes about Bastiat and his contemporaries, including his editor Prosper Paillottet, who became Bastiat's firm friend and eventually his executor. This section also includes discussions of key concepts such as individualism, laissez-faire, industry, plunder, and the right to work. Three glossaries explain persons, places, and subjects and terms.